2023
DOI: 10.3390/pharmaceutics15020467
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Felodipine from 3D-Printed Tablets with Constant Surface Area: Influence of Surface Geometry

Abstract: In this study, 3D-printed tablets with a constant surface area were designed and fabricated using polylactic acid (PLA) in the outer compartment and polyvinyl alcohol and felodipine (FDP) in the inner compartment. The influences of different surface geometries of the inner compartment, namely, round, hexagon, square, and triangle, on drug release from 3D-printed tablets were also studied. The morphology and porosity of the inner compartment were determined using scanning electron microscopy and synchrotron rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Specific surface area measurements are critical parameters for drug delivery systems, because they dictate various aspects such as pore size and volume, which govern [34,35].…”
Section: Surface Area Parameters Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific surface area measurements are critical parameters for drug delivery systems, because they dictate various aspects such as pore size and volume, which govern [34,35].…”
Section: Surface Area Parameters Evaluationsmentioning
confidence: 99%
“…This large surface area is very important for tissue regeneration, cell proliferation, and migration [37]. Moreover, it is a vital parameter for drug loading and release from porous nanomaterials [34,35].…”
Section: Surface Area Parameters Evaluationsmentioning
confidence: 99%
“…For example, Alvaro Goyanes and his team demonstrated that the release of tablets is independent of the surface area of a drug and depends on the surface-area-to-volume ratio (SA/V), which was determined using printing tablets with different geometries and by observing the rates of drug release [31]. This provided a reference for later researchers in developing different drug release rates via changing the geometries of drugs [32,33]. The red and blue clusters are mainly based on theoretical research on innovative topics such as technical method improvement and innovation [8,10,34].…”
Section: Co-citation Of Cited Referencesmentioning
confidence: 99%
“…In addition to changing the drug release rate by changing the substrate or drug formulation, other studies have shown that the surface area/volume ratio affects the drug release rate [33]. Under the condition of a constant surface area, the larger volume of a geometric shape increases porosity, resulting in faster drug release.…”
Section: Extended Release Of a Drugmentioning
confidence: 99%